2006
DOI: 10.1080/14649880600815917
|View full text |Cite
|
Sign up to set email alerts
|

Human Development: Beyond the Human Development Index

Abstract: The well-known Human Development Index (HDI) encompasses only three rather basic aspects of human welfare. This paper aims to go beyond this, by identifying 11 categories of human development. We next propose plausible candidates as indicators of these categories. We then estimate correlations among the indicators within each category, discarding those that are highly correlated with others. This left 39 indicators to encompass the categories. Of these, eight indicators are highly correlated with the HDI and m… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
102
0
17

Year Published

2011
2011
2023
2023

Publication Types

Select...
7
2
1

Relationship

0
10

Authors

Journals

citations
Cited by 207 publications
(119 citation statements)
references
References 10 publications
0
102
0
17
Order By: Relevance
“…McGillivray (1991), Trabold-Nubler (1991), Streeten, P. (1995), Morse (2003)). It does not take into account other dimensions of well-being, such as security, political participation and human rights Sen (1992, 2000), Ranis et al (2006)), or the distribution of human development within a country (Sagar and Najam, 1998, Grimm et al 2008. 1 Another criticism of the HDI is that it uses an essentially arbitrary weighting scheme of the three component indices, namely a simple average (Kelly (1991), Noorbakhsh, 1998;Srinivasan (1994), Ravallion (1997), Grimm et al (2008)).…”
Section: Introductionmentioning
confidence: 99%
“…McGillivray (1991), Trabold-Nubler (1991), Streeten, P. (1995), Morse (2003)). It does not take into account other dimensions of well-being, such as security, political participation and human rights Sen (1992, 2000), Ranis et al (2006)), or the distribution of human development within a country (Sagar and Najam, 1998, Grimm et al 2008. 1 Another criticism of the HDI is that it uses an essentially arbitrary weighting scheme of the three component indices, namely a simple average (Kelly (1991), Noorbakhsh, 1998;Srinivasan (1994), Ravallion (1997), Grimm et al (2008)).…”
Section: Introductionmentioning
confidence: 99%
“…Jedná se o index složený ze tří dílčích indikátorů, které měří úroveň vzdělání, zdravotní péče a životního standardu. HDI je však jen nepřesným a hrubým vyjádřením lidského rozvoje podle Senova přístupu, kritizován je mimo jiné pro absenci politických či environmentálních indikátorů nebo indikátorů příjmové nerovnosti (viz například Ranis et al, 2005nebo Syrovátka, 2008.…”
Section: Defi Nice Lidského Rozvoje a Ekonomického Růstuunclassified
“…Ranis et al (2005) stressed the need of neglecting some relevant dimensions and identified new categories encompassing all the major dimensions of human development. Sanusi (2008) implied that housing facilities and housing conditions increased the scope of human development, and thereby tried to widen the scope of issues covered by the HDI.…”
Section: Literature Reviewmentioning
confidence: 99%